DAMPAK KENAIKAN HARGA MINYAK GORENG TERHADAP INDUSTRI KECIL MENENGAH (IKM) DI KOTA TANJUNGPINANG TAHUN 2022 - Farisa Wulandari; Natasyaputri Sendhe Siregar; Riyan Tika Syafitri (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2022)
Cooking oil is one of the main ingredients that have commodities from nine basic materials that are strategic and have a multipurpose. And some time ago the increase in cooking oil prices had experienced a significant increase that was stunned which had an impact on human needs, especially small and medium industries (IKM) that produced using cooking oil. The purpose of this study was to determine the impact of the increase in cooking oil prices against the IKM in the city of Tanjungpinang, and overcome the problem of increasing the price of cooking oil against IKM. This research prioritizes the use of methods that are in accordance with the subject matter and in the research conducted. In order to obtain more specific and relevant data to be discussed further. This type of research uses descriptive research with a qualitative approach method. One of them is reduced, and for it is necessary to strategies from the IKM must remain the product of selling even though it only gets a little profit, if the sellers raise the price of the product, but if the price of cooking oil will drop it difficult to reduce production prices